2022
DOI: 10.3390/ph15050623
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-Group-Containing Thiopeptide Derivatives as Promising Agents to Target Clostridioides difficile

Abstract: The US Centers for Disease Control and Prevention (CDC) lists Clostridioides difficile as an urgent bacterial threat. Yet, only two drugs, vancomycin and fidaxomicin, are approved by the FDA for the treatment of C. difficile infections as of this writing, while the global pipeline of new drugs is sparse at best. Thus, there is a clear and urgent need for new antibiotics against that organism. Herein, we disclose that AJ-024, a nitroimidazole derivative of a 26-membered thiopeptide, is a promising anti-C. diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…difficile. Moreover, 6d exhibits elevated antibacterial activity against Enterococcus species (MIC 50 : 0.25 μg/mL), including vancomycin-resistant Enterococcus . Clinical observations have shown that patients with colonized Enterococcus species in the large intestine tend to exhibit a poor clinical prognosis if they become infected with C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…difficile. Moreover, 6d exhibits elevated antibacterial activity against Enterococcus species (MIC 50 : 0.25 μg/mL), including vancomycin-resistant Enterococcus . Clinical observations have shown that patients with colonized Enterococcus species in the large intestine tend to exhibit a poor clinical prognosis if they become infected with C.…”
Section: Resultsmentioning
confidence: 99%
“…The time-kill kinetics of 6d against ribotype 027 revealed a rapid onset of bactericidal action (Supporting Information). 39 Considering the low bioavailability of the compound, it is expected that its concentration in the large intestine would easily exceed the MIC value, resulting in rapid bactericidal action against C. difficile. Moreover, 6d exhibits elevated antibacterial activity against Enterococcus species (MIC 50 : 0.25 μg/mL), 39 including vancomycin-resistant Enterococcus.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, AJ-024, a nitroimidazole derivative of a 26-membered thiopeptide based on MP2, was proven to be a promising anti -C . difficile lead compound ( 32 ). Thus, MP2 could be a valuable platform for the development of new antibiotics.…”
Section: Introductionmentioning
confidence: 99%